Relationship of Exclusive Breastfeeding with The Incidence of Acute Respiratory Infections in Toddlers at The Ringinarum Health Center Kendal Regency - Izza Alya Ardana Putri; Astin Prima Sari; Ika Dyah Kurniati (Universitas Muhammadiyah Semarang, 2023)
Background: Acute Respiratory Infection (ARI) is an acute infection affecting the nose, paranasal sinuses, pharynx, trachea, bronchi, lungs, and epiglottis. ARI is the main cause of mortality and morbidity in toddlers in the world. The incidence of ARI can be prevented by exclusive breastfeeding.Objective: To prove the correlation of exclusive breastfeeding with the incidence of ARI in toddlersMethods: This case-control study conducted on December 2021 at the Ringinarum Health Center Kendal Regency. Sampling was conducted by purposive sampling method and was conducted based on inclusion and exclusion criterias.Results: The total samples obtained in this study were 124 samples. This study showed that the characteristics of toddlers with ARI among others the most frequent age is 24-35 months (30,6%), most of them were male (61,3%) and weren’t exclusively breastfed (69,4%). Futhermore, this study also found that there was a correlation between exclusivity of breastfeeding and the incidence of ARI in toddlers (p<0,05). Toddlers who weren’t exclusively breastfed had 5,5 times greater risk of ARI than those who were exclusively breastfed (OR>1).Conclusion: There is a correlation between exclusive breastfeeding with the incidence of acute respiratory infections in toddlers.